2019
DOI: 10.3390/agronomy9120804
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Guayulins to Improve Feasibility of Guayule Cultivation

Abstract: Guayule (Parthenium argentatum Gray) is an interesting alternative and renewable source of rubber/latex which has been used in the past. Guayule rubber and latex products are not available in the market largely because the raw material cost is higher than the current sources produced in South-East Asia and other tropical countries (Hevea brasiliensis). Guayule contains many other compounds whose joint exploitation could make guayule cultivation profitable, especially in semi-desert areas where cultivation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…This might open a new line of exploitation for guayule that would facilitate its commercialization. A caveat to this is that it clearly depends on whether it is easier or more difficult to extract these compounds, which is presumed to have fungicidal and acaricidal activity [ 7 ] from the leaves or stems. A priori the fact that the leaves have less rubber content could facilitate the extraction of the guayulins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might open a new line of exploitation for guayule that would facilitate its commercialization. A caveat to this is that it clearly depends on whether it is easier or more difficult to extract these compounds, which is presumed to have fungicidal and acaricidal activity [ 7 ] from the leaves or stems. A priori the fact that the leaves have less rubber content could facilitate the extraction of the guayulins.…”
Section: Discussionmentioning
confidence: 99%
“…Guayulin A was first isolated in 1911 and its structure was determined some years later [ 5 , 6 ]. Guayulins consist of an isoprenoid nucleus, which may be partheniol, with a bicyclogermacrene structure (Guayulins A and B), or its derivative compound with an aromadendrene structure (Guayulins C and D) [ 7 ], esterified either by trans -cinnamic acid (Guayulins A and C), or p -anisic acid (Guayulins B and D) [ 3 , 4 ] ( Figure 1 ). Guayulins have been described in high concentration in the resin component of the rubber plant commonly known as guayule ( Parthenium argentatum , Gray), a perennial shrub native to the Chihuauhan desert region of northern Mexico and Texas that does not produce the pseudoguaianolide sesquiterpene lactones found in almost all other species of the genus Parthenium [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As evergreen drought resistant shrubs might alleviate critical fodder shortage, the forage potential of guayule leaves is also being investigated [35]. This approach will contribute to exploitation of the whole plant biomass and non-rubber co-products not only for biobased by-products [14,[36][37][38], but also for complementing traditional activities. Additionally, it might contribute to support the interest in developing new agricultural commodities such as guayule for Mediterranean regions over the next years.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that finding and/or developing high-value resin-based products could significantly ameliorate the manufacturing cost of guayule rubber. 4 Previous studies on P. argentatum resin have resulted in the isolation of some major constituents including the cycloartane-type triterpenoids, argentatins A–C, 5 and the sesquiterpenoids, guayulins A–D, 6 whereas lanostane-type triterpenoids isoargentatins A and B, together with argentatins A–D, have been encountered in the roots of P. argentatum . 7 Investigation of the resin of the hybrid plant, P. argentatum × Parthenium tomentosum , has afforded two pyridine alkaloids, guayulamines A and B, 9 in addition to argentatins E–H, of which argentatins G and H were characterized as their diacetates.…”
Section: Introductionmentioning
confidence: 99%